Patching identity. How Russian language media in Estonia reconstitutes our understanding of citizenship - Polynin, Ivan (Frontiers in Political Science, 2023)
The conceptual novelty of this article rests in seeing identity not as a nominal category, but as a complex sequence of relationships between groups and narratives. It offers a deeper reading of Engin Isin's “citizenship in practice” and an empirical interpretation of how Andersen's imagined communities are brought to life through print media. Drawing from Raivo Vetik's analysis of the Estonian ethnopolitical field the author explores narratives of two major Russian language web-portals in Estonia: Rus.Postimees and Rus.Delfi. As a result, the reader may observe how the practice of citizenship simultaneously constitutes and is constituted by the minority's identity and subject position. The content analysis conducted from the samples of the aforementioned media outlets shows that the lack of shared citizenship practices between the majority and the minority causes a voluntary grouping along the lines of legal status, language, space and ethnicity. Discussing what constitutes Isin's act of citizenship the author concludes that acts are far more elusive than the ruptures they cause. A media analysis shows that aside from bearing long-term ruptures such as geographical, linguistic or formal, Estonian citizenship practice also received a new one, namely the symbolic rupture caused by the war in Ukraine. By breaking the previous status-quo, it pushes forward securitization and forces the minority to contest, redefine, and reestablish its allegiance and perceptions of its place in Estonian society.